The Effect of Compensation, Work Discipline, and Work Environment on Employee Performance: Evidence from an Indonesian Company - Agnar Rifky Iswanto; Nugraha Saefudin (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Employee performance is a critical determinant of organizational effectiveness and sustainability, particularly in labor-intensive organizations. This study aims to examine the effect of compensation, work discipline, and work environment on employee performance. A quantitative approach with a descriptive and verificative design was employed. The study included all 77 employees of PT Kriya Nusantara Global and employed a census sampling technique. Data were collected via structured questionnaires and analyzed using multiple linear regression, supported by validity and reliability assessments and classical assumption tests. The results indicate that compensation, work discipline, and work environment each have a positive and significant effect on employee performance. Furthermore, the simultaneous test confirms that these variables collectively explain significant variation in employee performance. The findings demonstrate that employee performance is shaped by an integrated human resource system that combines fair compensation, consistent disciplinary practices, and a supportive work environment. This study contributes to the human resource management literature by reinforcing the importance of integrated HR practices in improving employee performance. In practice, the findings provide managerial insights for organizations to design holistic HR policies that align reward systems, behavioral discipline, and workplace conditions to achieve sustainable performance improvements. However, the findings are based on a single-organization context and should be generalized with caution